Kann man in Japan von Nihilismus sprechen? Über die Rezeption Nietzsches bei Nishitani - Greco, Francesca (Scenari, 2021)
The main focus of my contribution will be nihilism in the form that Nishitani has elaborated in his confrontation with Nietzsche’s works and in his engagement with the events of his own time. In doing so, I intend to deal with the question of whether one can speak of nihilism in Japan, given its well-known European or Western roots, and if so, in what way. In order to prepare my question, I will first introduce the reader briefly to the reception of Nietzsche in Japan and report on Nishitani’s approach to Nietzsche’s thinking and to nihilism in general. Secondly, I will sketch the historical conditions of nihilism as they were relevant for Nietzsche and Nishitani in times of crisis, and I will distinguish between three forms of nihilism: direct, European and conscious nihilism. I will then describe the situation that led to the appropriation of nihilism in Japan. In what follows, I will deal with Nishitani’s interpretation of nihilism, the self-overcoming of which can be achieved thanks to the standpoint of emptiness, and I will present three main characteristics of such a standpoint that distinguish it from a destructive, annihilating perspective on the negativity of nothing: absolutely contradictory self-reference, negation and relationality. Finally, I will provide a brief overview of the subject under discussion in order to allow for concluding considerations on my initial question.